Synthesis and characterization of sodium bismuth titanate (Na0.5Bi0.5TiO3) ceramic by sol-gel method at different sintering temperature - Nurazlin, Ahmad (2016)
Sodium Bismuth Titanate is a prominent candidate for a lead-free piezoelectric material. In this research, Na0.5Bi0.5TiO3 was synthesized at different sintering temperature by sol-gel method in which the solutions were prepared by using sodium acetate CH3COONa, bismuth (III) acetate Bi(CH3COO)3, tetra-n-butyl titanate Ti(OC4H9)4, as starting materials. Acetic acid glacial and 2-methoxyethanol as solvents and acetylacetone as a reagent to stabilize tetra-n-butyl titanate. The obtained BNT powder was analyzed using XRD, FESEM, FTIR. The mechanical properties of BNT was determined by hardness testing to investigate the strength of the samples. Pellets have been formed and sintered at 940 oC, 960 oC, 980 oC, 1000 oC for 5 hours. The XRD analysis confirmed that the perovskite structure was obtained at each temperature.The effect of slightly different sintering temperature on the structural was studied in detail. FESEM analysis of pellets showed the well-developed grains having larger size at higher sintering temperature. Hardness analysis that was examined by using Rockwell hardness testing shows that hardness measurement increased as the sintering temperature increased due to the amount of strain or defect content in the compact powders.